Natural, human and spatial constraints to expanding populations of otters in the Iberian Peninsula - Clavero, Miguel; Hermoso, Virgilio; Brotons, Lluís; Delibes, Miguel (Journal of Biogeography, 2010)
Aim To determine the relationships between otter (Lutra lutra) distribution dynamics and environmental and spatial constraints over a 20-year period. Location Andalusia, southern Iberian Peninsula. Methods We synthesized otter distribution data from three otter surveys (1985, 1995 and 2005) using subcatchment areas defined by hydrological barriers. Subcatchments were characterized by two ‘natural’ (climatic and orographic variables) and two ‘human’ (land use and population density) gradients. In addition, we calculated two contagion variables (the distance to previously occupied subcatchments and the percentage of occupied subcatchments within a 50 km buffer) for consecutively surveyed subcatchments. Results Between 1985 and 2005 the percentage of subcatchments with otters present increased from 42% to 72%. Otters tended to be rare or absent from human-dominated areas. Anthropogenic gradients were better predictors of otter distribution than natural ones. Human and natural gradients showed strong covariation, but for any value of the natural gradients otters tended to be present in subcatchments with lower human impacts. Colonization of new subcatchments was found to be strongly related to contagion variables and expansion rates were slower than those estimated in other studies. Newly colonized areas tended to be located in areas with intermediate human influence, while repeated absences occurred mainly in areas where human impact was most severe. Main conclusions Our results suggest that recent otter expansion across Andalusia is a reflection of large-scale improvement in environmental conditions. Otter populations that survived the period of strong and generalized declines appear to be acting as sources from which neighbouring areas are colonized, probably aided by improved water quality and increases in food availability. However, the further expansion of otters into their full original range is likely to be constrained by human-impacted landscapes.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Andalusia; freshwater environments; landscape gradients; Lutra lutra; mammals; Mediterranean streams; otter surveys; recolonization; recovering species

Datos sobre la vegetación de andalucía. III. Series de vegetación caracterizadas por "Quercus suber" L. - Pérez Latorre, Andrés V.; Nieto, José M.; Cabezudo, Baltasar (Acta botánica malacitana, 1994)
Data about andalusian vegetation. III. Vegetation series with Quercus suber L. presence. Quercus suber woods are one of the natural forests with more diversity and more expanse in Andalusia (Spain). Quercus suber is a dominant or common species in eight vegetation series or subseries: Myrto communis-Querceto suberis S, Teucrio baetici-Querceto suberis S, Smilaci mauritanicae-Querceto rotundifoliae quercetoso suberis subsigmetum, Tamo communis-Oleeto sylvestris quercetoso suberis subsigmetum, San guisorbo hybridae-Querceto suberis S, Pyro bourgaeanae-Querceto rotundifoliae quercetoso suberis subsigmetum, Paeonio coriaceae-Querceto rotundifoliae quercetoso fagineae subsigmetum, var. of Quercus suber, Adenocarpo decorticantis-Querceto rotundifoliae quercetoso suberis subsigmetum. These vegetation series show peculiar sucesional dynamism of their communities depending on their traditional use, environmental factors and biogeographical location. Two new subasociations, Ulici eriocladi-Cistetum ladamferi cistetosum albidi and Phyllireo angustifoliae-Quercetum lusitanicae cytisetosurn tribracteojati, are described in this paper.
Keywords: Andalusia; Quercus suber woods; Spain; vegetation series